Joseph Lanner Chronologisch-thematisches Werkverzeichnis - Dörner, Wolfgang (2012)
Joseph Lanner (1801-18439 is one of the most important and outstanding composers of dance music in the so called "Biedermeier" (the period after the "Wiener Kongress", 1st half of the 19th century). He invented the form of the Viennese waltz and founded a tradition, which was successfully carried on by the Strauß-family. Although Lanner wrote more than three hundred compositions until now there is no list of works existing, which describes the existing sources. After more than five years of recherché this list of works is now completed. The first part gives an introduction and describes some of the attributes of Lanners compositions. A short biography is followed by chapters about the development of dance in Vienna at the beginning of the 19th century, a list of other dance music composers of that time, an overview of the forms Lanner used in his dances, but also specific themes such as instrumentation, a list of the most important halls where Lanner performed e.g. The second part is the list of works, ordered by works with Opus-number and works without. For every composition the user will find full information's about the instruments which are required in the composition, the existing editions including autographs, copies and music in print (as well as information's in which Viennese libraries these scores are available), information's about first performances and the person to whom the dance was dedicated, and references of newspapers or books in which the work is mentioned. At the beginning there are the incipients printed (for Ländler and waltz including first and second theme), which allows musicians all over the world to recognize a certain dance by the melody. In the appendices all works are listed once more by alphabetical order, furthermore you will find a list of all persons to whom a dance was dedicated and a short list of works of Lanners son, August. This list of works of the compositions of Lanner fulfils all criteria a modern list of works requires.